Poéticas visuais em construção: a metamorfose expressiva da criança e a educação (do) sensível - Schneider, Letícia Uhmann (2007)
This research, linked to the Teaching Post-Graduating Course, Arts Educational field, has been developed in a third (3rd) grade class of the Antônio Alves Ramos school, at the city of Santa Maria, RS. Aimed to know and analyze the under constructing creative process of the Initial Years children, providing time and space to the poetic action-experience, in the interacting with the education of the sensorial aspects. For that, articulates a dialogue with voices and ideas of Bachelard (1988, 1989, 1994), Richter (2005), Duarte Jr. (2001), Martins(1998), Maturana and Varela (2002) and Barbosa (2001, 2002). The methodology used in the research was based in the qualitative nature principles by the action-research. Presents itself as participant research, sustained by experiences of art poetics and fruition of daily school experience, emphasizing the imaginary, the creative process and dimension of being a person, not just the final artistic product. The instruments used for gathering data for this research were participative and free observation, field diary and portfolio. For that, in the creative process of children visual poetics, became obvious that the body carries a history - body time - and we can not teach them how to see, imagine, think or act like the adults. The act of creation demanded differentiated times, since each child understood the world in a different way, in their inexperience - another time aspect - admired, enamored, wondered, curious. The under constructing visual poetics allow with pleasure, internal discoveries which feed the person essence in a way to be able to feel, touch, mix, stick together, shape, plot, collect. Therefore, work with art is to believe in the tuning between pleasure and feeling, emotion and thought to construct a world of significance and significants. A world of colors, words, thoughts and actions, where art and knowledge interact on the poetic work and collaborate significantly in childish formation.